Efek Iradiasi Sinar Gamma Pada Tanaman Kacang Penutup Tanah (Mucuna bracteata L.) - Siti Hartati Yusida Saragih (JURNAL AGROPLASMA, 2021)
Legume cover crop (Mucuna bracteata L.) is a creeper which is currently often used to increase soil fertility in plantation areas. This plant is a leguminous plant that can fix nitrogen nutrients in the soil. One of the M.bracteata plant breeding programs to increase diversity is mutation using gamma ray radiation. The research objective was to determine the level of radiosensitivity of legume cover crop using gamma ray irradiation. The research was conducted at PAIR BATAN using a Gamma Chamber 4000A irradiator and in agricultural experiment, Labuhanbatu University. The plant material used was M.bracteata seeds with irradiation doses of 0, 200, 250, 300, 350 and 400 Gy. This study uses a curve fit analysis program to calculate the LD50 value (Lethal dose 50). The results showed that the plant radiosensitivity by calculating the LD50 value of M.bracteata at the age of 2 Weeks After Planting) was 348.737 Gy. The higher the radiation dose given, the lower the percentage of growth. Keywords: diversity; leguminous; lethal dosage; mutation; gamma rays